Associations between biomarker status (amyloid, tau) and risk for progression to MCI/Dementia in the Harvard Aging Brain Study. (December 2021) - Papp, Kate V.; Rentz, Dorene M.; Winskill, Carolyn; Betensky, Rebecca A.; Amariglio, Rebecca E.; Schultz, Aaron P.; Johnson, Keith A.; Sperling, Reisa A.
Abstract: Background: Previous reports have shown that elevated AD biomarkers among clinically normal (CN) older adults confer heightened risk for a subsequent diagnosis of cognitive impairment using CSF and amyloid imaging. Here, we examine the impact of biomarker status on neuroimaging for both amyloid(A+/A‐) and tau(T+/T‐) on risk for clinical progression. Method: Participants were CN at enrollment and underwent PET with 11C PiB to characterize global amyloid‐β(A) burden and F18 Flortaucipir (FTP) to quantify inferior temporal tau(T). Participants were dichotomized as A+/A‐ and T+/T‐ using previously described mixture model distribution cut‐points. Because FTP only became available mid‐study, we undertook two analytical approaches: 1) cox regression analysis with first PiB scan as time origin (n=342, follow‐up=6.10 years;range=1‐9) with tau treated as a time‐varying covariate (setting it to T‐ prior to the first FTP scan if T‐ and setting it to missing prior to first scan if T+) and 2) first FTP scan as time origin with tau treated as fixed at that time (n=242, follow‐up=5.12 years;range=1‐7). Participants were diagnosed annually by biomarker‐blinded case conference. Covariates included Demographics and E4(+/‐). Result: In the larger sample (31 individuals diagnosed with MCI/dementia), A+ was associated with increased diagnostic risk (HR=12.43, 95%CI=4.89‐31.57). In a model that included T as time‐varying (but not A), T+ was associated with increased risk for diagnosis (HR=4.46, 95% CI=0.99, 20.11, p=0.051). Including A in the model, A+ was associated with increased diagnostic risk (HR=5.30, 95%CI=1.29, 21.72) and T+ additionally appeared to confer higher risk, though not statistically significant (HR=2.89, 95%CI=0.12, 67.73). An interaction term was not significant (HR for A+T+ versus A+T‐=4.65, 95%CI=0.28, 77.79). In the smaller sample with tau (19 individuals diagnosed), T+ was also associated with greater risk for diagnosis (HR=3.61, 95%CI=1.38‐9.40). Older age (HR=1.09, 95%CI=1.02‐1.18) and E4+ (HR=5.40, 95%CI=1.96‐14.89) were contributory. Both A+ (HR=13.83, 95%CI=2.82‐67.81) and T+ (HR=2.75, 95%CI=1.05‐7.24) are associated with higher diagnostic risk when included in the same model. A+T+ was associated with higher risk(HR=2.59, 95%CI=0.98‐6.83, p=0.055) compared with A+T‐. Conclusion: A+ in combination with T+, is a significant risk factor for clinical progression. These findings provide further encouragement that interrupting A among CN older adults may mitigate risk for clinical progression.